The effectiveness of the use of gadgets in sports and physical education classes among students ("Journal "U". Economy. Management. Finance.", 2023)
This article discusses the possibility of introducing computer technologies in sports education for both sports fans and athletes, and students. Analyzed the latest gadgets for sports, as well as applications and devices for sleep, nutrition and other related elements of a healthy lifestyle.
Keywords: sports; sports gadgets; innovations; analysis of physical indicators; improvement of the quality of life